A Need Analysis English for Business Course - Sally, Sally; Pradana, Satria Adi (Universitas Islam Negeri Raden Intan Lampung, 2019)
English is an effective medium of communication in the world. The learners nowadays must capable of using English for a certain subject area. In academic, the use of English to learn subject area knowledge is increased, especially English for Specific Purposes (ESP). The need for ESP in business is to provide students with English following future professions so that they can become well-known business workers. In this study, needs analysis has been carried out to design ESP courses for management major students at Batam International University. This research study uses questionnaires for students and interviews for teachers and alumni. There are 4 English lecturers, 37 students from second semester students and 7 alumni who voluntarily participated in this study There are 3 components used in need analysis; present situation analysis (PSA) to find what learners’ strengths, weaknesses, skills, and experiences in English language; learning situation analysis (LSA) which concerned with learners’ learning preferences; and target situation analysis (TSA) to analysis more closely to learners’ reason for learning. ESP curriculum development must be seen from the needs of students. After analyzing the results, The results of the needs analysis help the lecturer to identify students' needs and weaknesses in language skills. After analyzing students' needs to determine the purpose of language courses, the lecturer can choose several materials according to the needs of students.